Sovereign Rents and Quality of Tax Policy and Administration - Knack, Stephen (2012)
Windfall revenues from foreign aid or natural resource exports can weaken governments' incentives to design or maintain efficient tax systems. Cross-country data for developing countries provide evidence for this hypothesis, using a World Bank indicator on "efficiency of revenue mobilization." Aid's negative effects on quality of tax systems are robust to correcting for potential reverse causality, to changes in the sample, and to alternative estimation methods. Revenues from natural resources are also associated with lower-quality tax systems, but results are somewhat sensitive to the choice of resource dependence indicators, and to a few extreme values in the data. Disaggregating by resource type, revenues from fuel exports are found to be more strongly associated than revenues from metals and ores exports with inefficient tax systems.